The Effect of Disaster Education Reslience Among Students In Indonesia: A Systematic Review - sukma, muthia; Fithria, Rahmi; Susanti, rika; Khanh, Varhanno K; Putra, Fariz Ananda; Salsabila, Mahira (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Background: Indonesia is highly prone to natural disasters, including floods, landslides, and earthquakes. Among the most vulnerable are children, particularly elementary school students. Disaster education is essential for enhancing their resilience and preparedness. Objective: This systematic review examines the impact of disaster education on the resilience of elementary school students in Indonesia, with a focus on how educational interventions improve disaster preparedness and psychological recovery. Methods: Following PRISMA guidelines, studies published between 2019 and 2024 were analyzed. Data were collected from ProQuest and EBSCO databases using keywords related to disaster education in Indonesian elementary schools. Included studies evaluated disaster education programs and their effects on students' resilience and preparedness. Results: Three studies met the inclusion criteria. Interventions, including 3D virtual simulations, moral comics, and traditional games, were found to effectively enhance disaster awareness and resilience. The review also highlights the importance of culturally relevant approaches to trauma recovery and emphasizes the need for a child-centered focus in disaster education. Conclusion: Disaster education significantly enhances the preparedness and resilience of Indonesian elementary school students. Integrating disaster education into school curricula and employing culturally appropriate methods are critical for building a more disaster-resilient generation. Broader implementation of these programs is necessary within Indonesia's education system.